1997
DOI: 10.1111/j.1432-1033.1997.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Amino Acids of Endonuclease VII Essential for Binding and Cleavage of Cruciform DNA

Abstract: Endonuclease VII is a Holliday-structure-resolving enzyme of bacteriophage T4. The active protein is a homodimer with 157 amino acidshonomer. An amber mutation (amE727 in codon 151) inactivates the nuclease completely, indicating the importance of the seven C-terminal amino acids for nucleolytic activity. The influence of these amino acids on cruciform-DNA binding and cleavage was investigated through functional analysis of C-terminal-truncated proteins derived from deletion constructs. It was found that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…T4 endo VII is a dimeric protein that binds preferentially to four-way DNA junctions in a Mg 2þ -and sequence-independent manner (Nishimoto et al 1979;Picksley et al 1990;Giraud-Panis and Lilley 1996;Pöhler et al 1996;Golz et al 1997). Interactions between the amino and carboxyl termini of different monomers are essential for DNA binding (Birkenbihl and Kemper 1998).…”
Section: T4 Endonuclease VIImentioning
confidence: 99%
“…T4 endo VII is a dimeric protein that binds preferentially to four-way DNA junctions in a Mg 2þ -and sequence-independent manner (Nishimoto et al 1979;Picksley et al 1990;Giraud-Panis and Lilley 1996;Pöhler et al 1996;Golz et al 1997). Interactions between the amino and carboxyl termini of different monomers are essential for DNA binding (Birkenbihl and Kemper 1998).…”
Section: T4 Endonuclease VIImentioning
confidence: 99%
“…21) or CFM13 (28 nucleotides/oligonucleotide; Ref. 22), a 600-bp centromeric region DNA from CEN3 of S. cerevisiae (23); and a 189-bp bent fragment from the Drosophila ftz scaffold-associated region (SAR) with an A/T content of 80% (24), full-length ss or ds M13mp18 and ⌽X174 DNA, and pBR322, pUC19 plasmid DNAs.…”
mentioning
confidence: 99%
“…A likely possibility is that UvsY induces a conformational change of Endo VII, thereby modulating the enzyme activity. Since we have recently shown that binding and cleavage reside in distinct functional domains of Endo VII (Golz et al, 1997) further studies are necessary to determine whether a modulation of Endo VII affects the DNA binding or the nucleolytic activity or both.…”
Section: Discussionmentioning
confidence: 99%